Leadership and the functioning of maternal health services in two rural district hospitals in South Africa. (8th July 2018) - Mathole, T; Lembani, M; Jackson, D; Zarowsky, C; Bijlmakers, L; Sanders, D
Abstract: Maternal mortality remains high in Eastern Cape Province, South Africa, despite over 90% of pregnant women utilizing maternal health services. A recent survey showed wide variation in performance among districts in the province. Heterogeneity was also found at the district level, where maternal health outcomes varied considerably among district hospitals. In ongoing research, leadership emerged as one of the key health systems factors affecting the performance of maternal health services at facility level. This article reports on a subsequent case study undertaken to examine leadership practices and the functioning of maternal health services in two resource-limited hospitals with disparate maternal health outcomes. An exploratory mixed-methods case study was undertaken with the two rural district hospitals as the units of analysis. The hospitals were purposively selected based on their maternal health outcomes: one reported good maternal health outcomes (pseudonym: Chisomo) and the other had poor outcomes (pseudonym: Tinyade). Comparative data were collected through a facility survey, non-participant observation of management and perinatal meetings, record reviews and interviews with hospital leadership, staff and patients to elicit information about leadership practices including supervision, communication and teamwork. Descriptive and thematic data analysis was undertaken. The two hospitals had similar infrastructure and equipment. Hospital managers at Chisomo used their innovation and entrepreneurial skills to improve quality of care, and leadership style was described as supportive, friendly, approachable but 'firm'. They also undertook frequent and supportive supervisory meetings. Each department at Chisomo developed its own action plan and used data to monitor their actions. Good performers were acknowledged in group meetings. Staff in this facility were motivated and patients were happy about the quality of services. The situation was different at Tinyade hospital. Participants described the leadership style of their senior managers as authoritarian. Managers were rarely available in the office and did not hold regular meetings, leading to poor communication across teams and poor coordination to address resource constraints. This demotivated the staff. The differences in leadership style, structures, processes and work culture affected teamwork, managerial supervision and support. The study demonstrates how leadership styles and practices influence maternal health care services in resource limited hospitals. Supportive leadership manifested itself in the form of focused efforts to build teamwork, enhance entrepreneurship and in management systems that are geared to improving maternal care.